2010
DOI: 10.1108/02683941011023749
|View full text |Cite
|
Sign up to set email alerts
|

Work‐family enrichment as a mediator between organizational interventions for work‐life balance and job outcomes

Abstract: PurposeThis paper aims to examine the role of work‐family enrichment in the relationships between organizational interventions for work‐life balance (job characteristics, work‐life benefits and policies, supervisor support and work‐family culture) and job outcomes (job satisfaction, affective commitment and organizational citizenship behaviour). It is hypothesized that organizational interventions for work‐life balance will be positively related to job outcomes and work‐to‐family enrichment will mediate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
210
5
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(245 citation statements)
references
References 81 publications
13
210
5
17
Order By: Relevance
“…Therefore, compared to males, females are more likely to display a negative attitude towards work when their work conflicts with family since they regard work as a threat to their main social role. However, according to gender role theory, when work conflicts with family, such a conflict is unlikely to cause males to change their attitude towards work (Grandey, Cordeiro, & Crouter, 2005;Baral & Bhargava, 2010). Males tend to feel less guilty conscious than females since the conflict they experience does not harm their social identity much, as a result of which their perception of WFC is different from that of females (Burke & El-Kot, 2010;Hassan, Dollard, & Winefield, 2010).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Therefore, compared to males, females are more likely to display a negative attitude towards work when their work conflicts with family since they regard work as a threat to their main social role. However, according to gender role theory, when work conflicts with family, such a conflict is unlikely to cause males to change their attitude towards work (Grandey, Cordeiro, & Crouter, 2005;Baral & Bhargava, 2010). Males tend to feel less guilty conscious than females since the conflict they experience does not harm their social identity much, as a result of which their perception of WFC is different from that of females (Burke & El-Kot, 2010;Hassan, Dollard, & Winefield, 2010).…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Commitment stemming from the parental role is associated with career satisfaction and performance, relates to a sense of enhancement, which reduces stress and strengthens positive outcomes. In addition, satisfaction with marriage has a significant relationship with job satisfaction [27] [28]. Experienced work/family enrichment may also have practical implications in terms of reducing the work absences incidence [29].…”
Section: Work-family Interface: the Positive And Negative Consequencesmentioning
confidence: 99%
“…For example, a study on work-family conflict among Malaysian employees has shown that informal workplace family support (such as greater discretion in managing work, and granting approval to leave work earlier than usual to deal with urgent family matters) has the potential of reducing work-family conflict (Aminah & Zoharah, 2013). Work-family facilitation can be enhanced by providing autonomy to employees (Baral & Bhargava, 2008;Innstrand et al, 2010;Siu et al, 2010) since autonomy is laden with resources including time-management skills, initiative, and self-confidence (Voydanoff, 2004) which could be applied to family activities. Another initiative is to increase employee job involvement since this is linked to work-family facilitation (Aryee et al, 2005).…”
Section: Discussionmentioning
confidence: 99%